Note sur le schisme ibadhite, à propos d'une lettre de M. Masqueray - Duveyrier, Henri (Bulletin de la Société de Géographie de Paris, 1878)

Notes on Socotra - Hunter, F. M. (The Journal of the Anthropological Institute of Great Britain and Ireland, 1878)
Keywords: Zanzibar

Les chroniques du Mezāb. Lettre de M. E. Masqueray à M. Duveyrier - Masqueray, Emile (Bulletin de la Société de Géographie, 1878)
Pp. 74-75: Note sur le schisme ibadhite, à propos d’une lettre de M. Masqueray, par Henri Duveyrier. On pp. 75-78, the letter of Masqueray. P. 76 (letter of Masqueray): I brought with me: the chronicle of Abū Zakariyyā’, the oldest and most complete chronicle; the chronicle on the lives of the sheikhs by sheikh Aḥmad; the books on the religious practices by Abū Zakariyyā’; and al-Nīl; this copy has been bought in Muscat. I will write on this Sidi Khalīl in a future work. Also: a MS by Muḥ. Iṭfayyish from Beni Isguen on the origin of the Ibāḍīs. A similar work by the Imam of Ghardaïa.
Keywords: Manuscrits – Mzab